2008
DOI: 10.1590/s0102-311x2008000600019
|View full text |Cite
|
Sign up to set email alerts
|

Adesão às precauções padrão pela equipe do atendimento pré-hospitalar móvel de Belo Horizonte, Minas Gerais, Brasil

Abstract: This was a cross-sectional study of workers in the pre-hospital care team in Belo Horizonte

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
1
36

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 13 publications
4
22
1
36
Order By: Relevance
“…Regarding the use of protec ve goggles, the data were similar to other studies that found a low adherence to this PPE (18)(19) . Despite all the orienta on and training about the recommenda on not to recap needles, there was s ll a signifi cant part of the sample who performed this procedure.…”
Section: Discussionsupporting
confidence: 86%
“…Regarding the use of protec ve goggles, the data were similar to other studies that found a low adherence to this PPE (18)(19) . Despite all the orienta on and training about the recommenda on not to recap needles, there was s ll a signifi cant part of the sample who performed this procedure.…”
Section: Discussionsupporting
confidence: 86%
“…Such differences may be related to academic training and varying function performed on the team (11) . Nevertheless, revealing that the higher the knowledge level of a professional category, the greater the chances for adopting precautionary measures, which in a way confirms the findings of this study in which the nursing assistant recognizes the availability of PPE less than the nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Non-adherence to standard precautions is worrying as it exposes the workplace to unnecessary occupational hazards and is reflected in high incidence rates of occupational accidents by exposure to body fluids and sharp objects (3,11) .…”
Section: Introductionmentioning
confidence: 99%
“…8 The recommended measures include hand hygiene and the use of individual protection equipment. [8][9] In Brazil programs for prevention and control of HAIs are required by law (9.431/1997) in all hospitals, and a decree (2.616/1998) states the directives and norms for the prevention and control of such events, along with the suggested measures. [9][10][11] Nevertheless, the difficulty of complying with the cited scientific and governmental recommendations in Brazilian hospitals is recognized, even in wealthier regions of the country, due to the disparities of care characteristics and availability of resources.…”
Section: Discussionmentioning
confidence: 99%